(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3YKeGf Hf YHO GdQMef Hf MeRIs)
(3ChdgG (B:s
(3ShQI jS ecjI jS cCde aj GdeYfi hGdEYQGH hbjd eYfGg(B: (3jG EfSGf HdZI WjAs
(3BNQgG (B:s
(3aEf fSjGf Mb Gddg jYe GdKbdjf Yf GdfHj ef bQC GdeYhPJjf acCfeG bQC GdcJH GdJj CfRdgG Gddg JYGdi cdgG Jes
(3HChdgG agQSs
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdHjVGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/109s
(3cTa GdXfhf (B1/186s
Keywords: (3GdJaSjQ hYdhe GdbQBfs